First human case of severe septicaemia associated with Mycoplasma capricolum subsp. Capricolum infection - Heller, M.; Schwarz, R.; Noe, G.; Jores, Joerg; Fischer, A.; Schubert, E.; Sachse, K. (Microbiology Society, 2015)
Introduction: The bacterium Mycoplasma capricolum subsp. capricolum is known as a pathogen in goats. There have been no reports on a zoonotic potential so far. Case presentation: A case of septicaemia and meningoencephalitis in a 62-year-old patient has been associated with infection by M. capricolum subsp. capricolum. No other infectious agent could be detected. Conclusion: Although it was impossible to identify the source of infection, coincidental contact with small ruminants or consumption of food products from goats during a tourist trip may have played a role.